2020
DOI: 10.1177/1120672120951760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraoperative lagophthalmos formula for levator resection in congenital ptosis in Egyptian patients

Abstract: Purpose: To evaluate the recent intraoperative lagophthalmos formula method for levator resection in determining postoperative lid height in congenital ptosis on Egyptian patients. Methods: This is a prospective case series which included 20 eyelids of 17 Egyptian children with congenital ptosis whose levator function is 4 mm or better. They underwent levator muscle resection guided by the recently presented intraoperative lagophthalmos formula. Preoperative Margin-to-Reflex Distance 1 (MRD1) and levator funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…When compared with the previously reported surgical success rates of congenital ptosis surgeries, ranging from 47% to 93%,8–14 the IOLF seems to yield promising surgical results. Recently, an Egyptian study group used the IOLF for levator resection in 20 eyelids of 17 patients with congenital ptosis involving LF ≥4 mm and reported a satisfactory outcome of up to an 80% success rate 15. In the present study of 30 eyelids of 22 patients, we also confirmed the usefulness of the IOLF based on LF: the success rate was 100% (n=19/19) in eyelids with LF ≥5 mm, versus 72.7% (n=8/11) in eyelids with LF normal≤ 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with the previously reported surgical success rates of congenital ptosis surgeries, ranging from 47% to 93%,8–14 the IOLF seems to yield promising surgical results. Recently, an Egyptian study group used the IOLF for levator resection in 20 eyelids of 17 patients with congenital ptosis involving LF ≥4 mm and reported a satisfactory outcome of up to an 80% success rate 15. In the present study of 30 eyelids of 22 patients, we also confirmed the usefulness of the IOLF based on LF: the success rate was 100% (n=19/19) in eyelids with LF ≥5 mm, versus 72.7% (n=8/11) in eyelids with LF normal≤ 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods are available to calculate the amount of levator resection based on levator function, MRD1 and intraoperative lagophthalmos [ 4 ]. However, to the best of our knowledge, there is no formula specifically tailored for the levator muscle plication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Such type of surgical audit is a useful tool to assess shortcomings and are important source to guide and improve results. 10 It is beneficial both for the surgeon as well as the patients. We compared our results with different studies.…”
Section: Introductionmentioning
confidence: 99%